DETERMINAN KETIMPANGAN PEMBANGUNAN EKONOMI ANTARPROVINSI DI INDONESIA - Anin Nabail Azim; Hady Sutjipto; Rah Adi Fahmi Ginanjar (Universitas Pasundan, 2022)
This study aims to determine and understand the determinants of inequality in economic development between provinces in Indonesia. The analysis is carried out by first calculating the Williamson Index as an indicator of inequality in economic development between regions. They used economic and social variables, including the human development index, road infrastructure, and foreign investment. This research method uses a statistical panel data approach with the Fixed Effect Model (FEM) model. This study explains that the human development index partially has a significant negative effect on inequality between regions. Road infrastructure and foreign investment have a significant positive impact on inequality between regions. Simultaneously, the human development index, road infrastructure, and foreign investment significantly affect economic development inequality between regions.